2016
DOI: 10.1186/s12885-016-2834-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of anti-VEGF and anti-EGFR attenuates the growth and angiogenesis of colorectal cancer mainly through suppressing AKT and ERK signaling in mice model

Abstract: BackgroundAngiogenesis is generally involved during the cancer development and hematogenous metastasis. Vascular endothelial growth factor (VEGF) and epidermal growth factor receptor (EGFR) are considered to have an important role in tumor-associated angiogenesis. However, the effects of simultaneously targeting on VEGF and EGFR on the growth and angiogenesis of colorectal cancer (CRC), and its underlying mechanisms remain unknown.MethodsImmunohistochemical staining was used to detect the VEGF and EGFR express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 54 publications
1
28
0
1
Order By: Relevance
“…Increased STAT3 activity can promote protein dimerization and translocation to regulate expression of critical genes such as cell survival Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry factors [42][43][44], signaling pathways [45,46], and MnSOD activity in mitochondria [47]. We determined JAK2 expression provided insight into the mechanisms of O-GlcNAcylation on p705STAT3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Increased STAT3 activity can promote protein dimerization and translocation to regulate expression of critical genes such as cell survival Cellular Physiology and Biochemistry Cellular Physiology and Biochemistry factors [42][43][44], signaling pathways [45,46], and MnSOD activity in mitochondria [47]. We determined JAK2 expression provided insight into the mechanisms of O-GlcNAcylation on p705STAT3 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Wheler and colleagues demonstrated that cetuximab and erlotinib combination was well tolerated and five out of 20 patients (25%) had achieved partial response and stable disease ≥ 6 months in patients with NSCLC [35]. VEGF and EGFR signaling pathways are intercorrelated; via up-regulating VEGF by EGFR expression and VEGF up-regulation independently contributing to EGFR resistance [29,[38][39][40][41]. Preclinical evidence suggested that inhibiting both pathways suppress AKT and ERK signaling and have notably shrunken the tumor growth in CRC cells lines [39].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF and EGFR signaling pathways are intercorrelated; via up-regulating VEGF by EGFR expression and VEGF up-regulation independently contributing to EGFR resistance [29,[38][39][40][41]. Preclinical evidence suggested that inhibiting both pathways suppress AKT and ERK signaling and have notably shrunken the tumor growth in CRC cells lines [39]. In preclinical models and early phase trials, combination of VEGF and EGFR inhibition has shown activity in advanced solid tumors, including CRC, NSCLC, breast cancer, renal cell carcinoma and HNSCC [28,[42][43][44].…”
Section: Discussionmentioning
confidence: 99%
“…AKT and ERK are serine/threonine kinases that are critical for many diverse processes, including cell proliferation, apoptosis, migration, angiogenesis and metastasis (28)(29)(30)(31). IQGAP1, as a scaffold protein, contains multiple domains which mediate binding to a number of proteins.…”
Section: Discussionmentioning
confidence: 99%